Timing of second polar body extrusion and pronuclear formation after intracytoplasmic sperm injection (ICSI) - Suwit Suppinyopong (2018)
To determine timing of second polar body extrusion and pronuclear formation to find out when the intracytoplasmic sperm injected (ICSI) oocytes should be checked for successful fertilization. 148 oocytes from 15 patients from January to May 1998 were analyzed. Metaphase II oocytes were followed by ICSI. Fertilization was checked at 2, 4, 6, 8, 16 and 18 hours later for observation of second polar body extrusion and pronuclear formation. Normal fertilization was achieved in 73.6 per cent of the oocytes (109/148). After ICSI at 2, 4, 6, 8, 16 and 18 hours, extrusion of second polar body was 8.3 per cent, 49.5 per cent, 84.4 per cent, 98.2 per cent, 98.2 per cent, 98.2 per cent and pronuclear formation was O per cent, O per cent, 8.3 per cent, 30.3 per cent, 96.3 per cent, 100 per cent respectively. The earliest extrusion of second polar body and pronuclear formation were at 2 and 6 hours after ICSI respectively. This study suggests that the appropriate time to determine fertilization is at 2, 6 and 18 hours after ICSI.